Improved Automatic Inoculator for Bacterial Cultures - Maier, S. (1970)
A simple automatic inoculator which allows the simultaneous inoculation of several cultures with identical or different inocula is described. The use of Teflon spaghetti tubing allows great flexibility in handling and placing of components. The inoculator can be adapted to handle aerobic and anaerobic bacteria.